BMI Trajectories During the First 2 Years, and Their Associations With Infant Overweight/Obesity: A Registered Based Cohort Study in Taizhou, China - Zhang, Tian; Song, Ying; Teng, Haoyue; Zhang, Yue; Lu, Jianan; Tao, Linghua; Jin, Yanjie; Yin, Jieyun; Zhou, Danhong (Frontiers in Pediatrics, 2021)
Objective: The purpose of this study was to identify trajectories of body mass index (BMI) in toddlers from birth to 2 years old and examine their association with infantile overweight/obesity. Methods: Data were collected from 19,054 children born in any hospital or community healthcare center in Taizhou, China from 2018 to 2019 with at least three BMI measurements after birth. The Latent Class Growth Mixture Model was used to identify distinct BMI trajectories during the first two years of infants. Multiple logistic regression models were conducted to explore the associated factors of different BMI trajectories, and log-binomial regression was performed to assess the association between the trajectories and overweight/obesity. Results: Three heterogeneous BMI trajectories were identified and labeled as ‘lower’ (36.21%, n=6,899), ‘middle’ (53.15%, n=10,128) and ‘upper’ (10.64%, n=2,027), respectively. Several characteristics of infants and their corresponding mothers were found to be correlated with infant BMI trajectories, including infant sex, mode of delivery and weight at birth, as well as maternal parity, early pregnancy BMI and status of gestational diabetes mellitus. Furthermore, compared with those in the lower trajectory, infants in the middle [prevalence ratio (PR)=2.63, 95% confidence interval (95%CI)=2.17-2.63] or upper (PR=2.98, 95%CI=1.51-2.98) trajectory groups were prone to be overweight/obesity at their final observation. Conclusion: Heterogeneous BMI trajectories were observed in our study. Characteristics of both infants and their corresponding mothers could be potential determinants of infant growth. Moreover, infants in the middle and upper trajectory groups were more likely to suffer overweight/obesity.